Intravenous immunoglobulin induces IL-4 in human basophils by signaling through surface-bound IgE - Galeotti, Caroline; Stephen-Victor, Emmanuel; Karnam, Anupama; Das, Mrinmoy; Gilardin, Laurent; Maddur, Mohan S.; Wymann, Sandra; Vonarburg, Cédric; Chevailler, Alain; Dimitrov, Jordan D.; Benveniste, Olivier; Bruhns, Pierre; et al. (Journal of allergy and clinical immunology, 2019)
Therapeutic normal IgG or intravenous immunoglobulin (IVIG) exerts anti-inflammatory effects through several mutually nonexclusive mechanisms. Recent data in mouse models of autoimmune disease suggest that IVIG induces IL-4 in basophils by enhancing IL-33 in SIGN-related 1–positive innate cells. However, translational insight on these data is lacking. We sought to investigate the effect of IVIG on human basophil functions. Isolated circulating basophils from healthy donors were cultured in the presence of IL-3, IL-33, GM-CSF, thymic stromal lymphopoietin, or IL-25. The effect of IVIG and F(ab')2 and Fc IVIG fragments was examined based on expression of various surface molecules, phosphorylation of spleen tyrosine kinase, induction of cytokines, and histamine release. Basophil phenotypes were also analyzed from IVIG-treated patients with myopathy. Approaches, such as depletion of anti-IgE reactivity from IVIG, blocking antibodies, or inhibitors, were used to investigate the mechanisms. We report that IVIG directly induces activation of IL-3–primed human basophils, but IL-33 and other cytokines were dispensable for this effect. Activation of basophils by IVIG led to enhanced expression of CD69 and secretion of IL-4, IL-6, and IL-8. IVIG-treated patients with myopathy displayed enhanced expression of CD69 on basophils. The spleen tyrosine kinase pathway is implicated in these functions of IVIG and were mediated by F(ab')2 fragments. Mechanistically, IVIG induced IL-4 in human basophils by interacting with basophil surface-bound IgE but independent of FcγRII, type II Fc receptors, C-type lectin receptors, and sialic acid–binding immunoglobulin-like lectins. These results uncovered a pathway of promoting the TH2 response by IVIG through direct interaction of IgG with human basophils. [Display omitted]